The frequency of C609T polymorphism in the NQO1 gene and its relation to cytogenetic abnormalities in patients with myelodysplastic syndrome - Bagatir, G; Sirma, S; Palanduz, S; Ozturk, S; Cefle, K; Ozbek, U; Yenerel, M; Nalcaci, M (Cellular and Molecular Biology, 2016)
The aim of the present study is to evaluate the frequency of C609T polymorphism in the NQO1 (NAD(P)H) quinon oxydoreductase) gene and its relation to cytogenetic abnormalities in patients with Myelodysplastic Syndrome (MDS). The study group consisted of 80 patients MDS with 13 of them in the pediatric age group. The frequency of the NQO1 gene polymorphism was compared with a healthy control group involving 423 individuals. Cytogenetic abnormalities were detected in 43 patients (54%). In patients with MDS the overall frequency of the C609T polymorphism was not different than controls. Also, although the frequency of the C609T polymorphism was higher in patients with secondary MDS (sMDS) (OR: 1.893, 95% CI: 0.840-4.265, p=0.238) , 5/del(5q) (OR:1.298, 95% CI: 0.331-5.086,p=0.124), +21(OR:1.817, 95% CI:0.429-7698,p=0.124) and t(8;21) (OR:3.028, 95% CI: 0.604-15.172,p=0.137) groups, the difference did not reach statistical significiance. Our results do not support the view that the C609T polymorphism has a role in the pathogenesis of MDS. Also the frequency of the C609T allele did not seem to be associated with cytogenetic abnormalities.